Analysis of Hospital Image and Availability of Human Resources on The Utilization of Outpatient Services in Arjawinangun Regional Hospital Cirebon - Albertin Jane Agung Tanusantoso; Alih Germas; Yeny Sulistyowati; Bambang Sumardi (CV. Inara, 2026)
Outpatient services are the primary gateway for patients entering healthcare facilities, yet declining visits at regional hospitals in Indonesia indicate challenges in service utilization. This study aims to describe outpatient service utilization in relation to hospital image and human resource availability at Arjawinangun Regional Hospital, Cirebon. A quantitative descriptive study was conducted with 128 outpatients selected through simple random sampling. Data were collected using a structured questionnaire adapted from previous studies, consisting of 12 items for hospital image, 12 items for human resource availability, and 20 items for outpatient service utilization, all measured on a five-point Likert scale. Descriptive analysis was performed using IBM SPSS Statistics to calculate mean scores, which were interpreted using categories of very poor, poor, good, and very good. The results show that hospital image achieved an overall mean of 4.11 (very good), with functional image scoring highest (4.27) and institutional image lowest (3.98). Human resource availability achieved an overall mean of 4.06 (very good), with discipline and work ethic scoring highest (4.11) and waiting time concerns scoring lowest (3.88). Outpatient service utilization achieved an overall mean of 4.05 (very good), with service accessibility scoring highest (4.15) and visit frequency scoring lowest (3.96). The study concludes that while patient perceptions of hospital image and human resources are generally very positive, institutional transparency, waiting time management, and visit frequency require strategic attention. These findings provide empirical evidence for hospital management to strengthen institutional image and optimize staff distribution to enhance consistent outpatient service utilization.